Effect of information, education, and communication activity on health literacy of smoking and alcohol among school-going adolescents in Delhi - Srishti Yadav; Anita Khokhar (Wolters Kluwer Medknow Publications, 2019)
Background: Noncommunicable diseases (NCDs)/lifestyle diseases account for a major cause of deaths every year. Risk factors such as smoking and alcohol consumption contributing to the development of lifestyle diseases were more prevalent in the developed countries decades back, but millions of productive years of life are lost due to NCDs in India too. Objective: This study was conducted to assess the health literacy of school-going adolescents regarding harmful effects of smoking and alcohol consumption and assess the improvement in their knowledge after different information, education, and communication (IEC) activities. Methods: It was a school-based interventional study conducted among students of class 6, 7, and 8. Assessment of health literacy of risk factors - smoking and alcohol use in lifestyle diseases was done by self-administered questionnaire among school-going adolescents. Intervention in the form of IEC was done three times, and the postintervention data were collected 2 weeks after the first and 3 months after the last intervention. Responses were scored and categorized as satisfactory and unsatisfactory. Results: There were a higher proportion of students with satisfactory level of knowledge of smoking and alcohol use effects in both the schools after 3 months of educational intervention, although the result was statistically significant for School 2 only where intervention was given by didactic lectures (P < 0.05). Conclusions: There was an improvement in scores of students in both the schools after 2 weeks and 3 months of educational intervention, though the results were statistically significant for 3 months only (P < 0.05).